Relational Trauma: Psychodynamically Informed Communication for Serious Illness Care - Indrany Datta-Barua; Keri O. Brenner; Danielle Chammas; Margaret A. Cramer (Journal of Palliative Medicine, 2026)
Patients with relational trauma , including histories of maltreatment, abandonment, exploitation, or profound misattunement in caregiving relationships, may face unique psychological and interpersonal stressors when diagnosed with a serious illness. Because serious illness requires dependence on others, patients’ past traumatic experiences with caregivers may be reactivated in medical relationships, manifesting in behaviors that can be confusing, contradictory, inconsistent, or difficult to understand. These dynamics may evoke intense countertransference responses in clinicians, at times making it difficult to offer therapeutically attuned care. By understanding relational trauma through the lens of psychodynamic and neuropsychological principles, palliative care clinicians can develop more empathic and clinically useful approaches to managing complex interpersonal dynamics. This article illustrates how these principles can be adapted to inform serious illness communication strategies for patients with relational trauma, including calibrating the treatment frame, validating emotions while maintaining boundaries, enhancing empathy to promote the therapeutic relationship, and repairing ruptures in the treatment relationship.